Investigation On The Current Amplification For Multiple Input RF Energy Harvester Circuit - Md Fuad, Muhammad Aiman (Universiti Teknologi PETRONAS, 2016)
RF (radio frequency) is one of ambient energy surrounding us that able to change state of energy to electricity. RF harvesting circuits have been experimented for a longer period in order giving option on electricity. Low powered equipment or sensors can be powered up from this ambient energy and last long instead using dry cell that worn out by time. Previous final year project able to come out with antenna that able to extract electricity from RF but then produce very low power. Thus, this project should come out with current amplification module circuit for single source.